Dampak Pengaruh Game Online Terhadap Prestasi Belajar Siswa - Karolus Wulla Rato; Anselmus Kartino Beong; Anjela Lende; Yuliana Saibel; Yuliana Ina Kalanda; Rosalia Rambu Padu Leba; Velikia Rau Rengu; Yulius Ngongo; Marten Saingo (Badan Penerbit STIEPARI Press, 2025)
This study aims to examine the impact of the frequency of playing online games on the academic performance of middle school students. Using a quantitative approach, the research involved 150 students randomly selected from several schools in city X. Data were collected through questionnaires about the duration of online game play and academic scores, which were then analyzed using Pearson correlation tests and simple linear regression. The results showed a significant negative correlation between the duration of online game play and students' academic performance (r = -0.62, p < 0.01). This means that the more time students spend playing online games, the lower their academic achievements. Regression analysis revealed that online game play accounted for 38.4% of the variation in academic performance. These findings suggest that excessive online gaming can interfere with students' focus and motivation to study. Therefore, it is important for students, parents, and educators to regulate the time spent on online games to avoid negatively impacting learning quality. This study also highlights the importance of good time management as a key factor in supporting students' academic success in the digital age.